Perceived team motivational climate, athletic identity, and academic endeavors among high school athletes - Chamberlin, J. M.; Fry, M. D.; Long, H.; Iwasaki, S. (Journal of Clinical Sport Psychology, 2026)
The purpose of this study was to examine whether athletes` perceptions of a caring (C) and task-involving (TI) sport climate significantly predict their career decision self-efficacy; career exploration and engagement; academic support from coaches and teammates; and athletic and academic identity, after controlling for athletes` demographic information. High school athletes (N = 228; 75 females and 146 males) completed a survey that included the measures of interest. A series of hierarchical regression analyses revealed that students` perceptions of a C/TI climate were positive predictors of their career decision self-efficacy (TI), academic identify (TI), and coach support of their academics (C/TI). The findings of this study build on the work of Poux and Fry published in 2015 with college athletes. When coaches foster a C/TI climate, they may be promoting holistic development of their athletes by encouraging them to invest in their academic program and prepare for future careers.